Neonatal brain injury causes cerebellar learning deficits and Purkinje cell dysfunction - Aaron Sathyanesan (Nature Portfolio, 2018)
Premature infants are vulnerable to hypoxia and thus white matter injury, especially in the cerebellum, which develops during late gestation. Here, the authors test the effects of perinatal hypoxia on motor performance and rescue behavioral deficits using the GABA reuptake inhibitor Tiagabine.